Fundamental and application aspects of adsorption cooling and desalination. (25th March 2016) - Saha, Bidyut Baran; El-Sharkawy, Ibrahim I.; Shahzad, Muhammad Wakil; Thu, Kyaw; Ang, Li; Ng, Kim Choon
Highlights: Adsorption characteristics of various adsorbent–refrigerant pairs have been investigated. Adsorption cycle for sea water desalination has been introduced. Introduced the performance of hybridized adsorption and thermally driven cycle. Presented the costing of desalination methods by energetic and exergetic approaches. Graphical Abstract: Abstract: Adsorption (AD) cycle is recently pioneered for cooling and desalination applications. For water treatment, the cycle can be used to treat highly concentrated feed water, ranging from seawater to ground water and to chemically-laden waste water. This paper presents a review of the recent development of AD cycle and its hybridization with known conventional cycles such as the MED and MSF. We begin by looking at the basic sorption theory for different adsorbent–adsorbate pairs, namely (i) silica gel-water, (ii) the zeolite–water, (iii) parent Maxsorb III/ethanol, (iv) KOH-H2 surface treated Maxsorb III/ethanol, and (v) a metal organic framework (MOF) material namely, MIL-101Cr/ethanol. We also present the basic AD cycle for seawater desalination as well as its hybridization with known conventional thermally-driven cycles for efficiency improvement. We demonstrate the water production improvement by 2–3 folds by hybridization in a pilot comprising a 3-stage MED and AD plant and the top-brine temperature 50 °C.